VEGF Pathways in the Lymphatics of Healthy and Diseased Heart. (January 2016) - Dashkevich, Alexey; Hagl, Christian; Beyersdorf, Friedhelm; Nykänen, Antti I.; Lemström, Karl B.
Abstract: Cardiac lymphatic system is a rare focus of the modern cardiovascular research. Nevertheless, the growing body of evidence is depicting lymphatic endothelium as an important functional unit in healthy and diseased myocardium. Since the discovery of angiogenic VEGF‐A in 1983 and lymphangiogenic VEGF‐C in 1997, an increasing amount of knowledge has accumulated on the essential roles of VEGF ligands and receptors in physiological and pathological angiogenesis and lymphangiogenesis. Tissue adaptation to several stimuli such as hypoxia, pathogen invasion, degenerative process and inflammation often involves coordinated changes in both blood and lymphatic vessels. As lymphatic vessels are involved in the initiation and resolution of inflammation and regulation of tissue edema, VEGF family members may have important roles in myocardial lymphatics in healthy and in cardiac disease. We will review the properties of VEGF ligands and receptors concentrating on their lymphatic vessel effects first in normal myocardium and then in cardiac disease.